Solid-State Random Lasers - Noginov, Mikhail A.; SpringerLink (Online service) (New York, NY : Springer New York, 2005)
Random lasers are the simplest sources of stimulated emission without cavity, with the feedback provided by scattering in a gain medium. First proposed in the late 60$1 (Bs, random lasers have grown to a large research field. This book reviews the history and the state of the art of random lasers, provides an outline of the basic models describing their behavior, and describes the recent advances in the field. The major focus of the book is on solid-state random lasers. However, it also briefly describes random lasers based on liquid dyes with scatterers. The chapters of the book are almost independent of each other. So, the scientists or engineers interested in any particular aspect of random lasers can read directly the relevant section. Researchers entering the field of random lasers will find in the book an overview of the field of study. Scientists working in the field can use the book as a reference source.s
Lasers with Nonresonant Feedback and Laserlike Emission from Powders: Early Ideas and Experiments -- Neodymium Random Lasers: Experimental Studies of Stimulated Emission -- Propagation of Light in Neodymium Random Lasers -- Theoretical Modeling of Neodymium Random Lasers -- Engineering Aspects of Neodymium Random Lasers: External Seeding, Design, and Second Harmonic Generation -- Random Lasers Pumped with Electron Beam -- Semiconductor Random Lasers -- Dye and Polymer Random Lasers -- Other Types of Solid-State Random Lasers -- Applications of Random Lasers.
Keywords: Physics; Quantum optics; Condensed matter; Physics; Quantum Optics; Condensed Matter Physics; Electronic books